Motivation as a Bridge Between Training, Coaching, and Employee Performance: Motivasi sebagai Jembatan Antara Pelatihan, Pembinaan, dan Kinerja Karyawan - Deny Fahrianur; Zainal Ilmi; Siti Maria (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Regional-owned enterprises (BUMD) play a vital role in supporting regional development and economic independence in Indonesia, particularly within the energy sector of East Kalimantan. Specific Background: Despite their strategic position, many BUMDs face challenges in maintaining competitiveness due to limited human resource development and weak managerial systems. Knowledge Gap: Prior studies have examined the effects of training and motivation on employee performance, but few have explored the mediating role of motivation between training, coaching, and performance in regional energy enterprises. Aims: This study investigates how training and coaching influence employee performance through motivation as a mediating variable. Results: Using an explanatory survey method with 82 respondents and Partial Least Squares (PLS) analysis, findings reveal that training and motivation significantly affect performance, coaching affects motivation but not performance directly, and motivation mediates the relationship between both predictors and performance. Novelty: This research highlights motivation as a pivotal mediating mechanism linking developmental interventions to performance in the regional energy industry context. Implications: The study underscores the importance of integrating structured training and personalized coaching to strengthen employee motivation, thereby enhancing organizational performance and sustainability within the energy sector. Highlights: Motivation mediates the link between training, coaching, and performance. Coaching enhances motivation more strongly than direct performance. Integrated HR development boosts competitiveness in the energy sector. Keywords: Training, Coaching, Motivation, Employee Performance, Energy Industry